Fatigue assessment of welded and high frequency mechanical impact (HFMI) treated joints by master notch stress approach. (August 2017) - Leitner, Martin; Stoschka, Michael; Ottersböck, Markus
Highlights: Presentation of HFMI master model based on notch stress approach. Model enables a local fatigue assessment of complex welded structures. Validation including over 230 constant and variable amplitude fatigue test results. Abstract: High frequency mechanical impact (HFMI) treatment is a reliable and utmost effective method for post-weld fatigue strength improvement of steel joints, especially in case of high-strength steel applications. In 2014, the HFMI master notch stress approach was firstly introduced as an alternative design concept. It features an engineering-feasible method to assess the notch fatigue strength of HFMI-treated joints based on weld toe notch stress concentration, base material yield strength and load stress ratio. This paper presents an essential update of the HFMI master notch stress approach by facilitating the notch factor KW, obtained as the ratio of effective notch stress σk to structural stress σs . This enables a thorough fatigue assessment of welded structures without the need of a nominal cross-section definition. To proof the applicability, a comprehensive validation of the HFMI master notch stress approach incorporating over 230 additional steel joint specimen results covering both constant and variable amplitude tests is conducted. The constant amplitude study reveals that the fatigue strength of the HFMI master notch stress approach, utilizing the notch factor KW, is well applicable for material strengths up to ultra high-strength steels with a nominal yield limit of 1300 MPa. In addition, the notch stress based service strength evaluation of variable amplitude loaded HFMI-treated high-strength steel joints considering a specified damage sum of D = 0.3 according to Sonsino can be also well utilized for HFMI-treated joints.